Financial repression, liberalization and bank total factor productivity: empirical evidence from the Thailand banking sector - Sufian, Fadzlan (Academy of Economic Studies, 2011)
The present paper employs the Malmquist Productivity Index (MPI) method to examine sources of total factor productivity change of the Thailand banking sector during the post-Asian financial crisis period of 1999-2008. The empirical findings suggest that the Thailand banking sector has exhibited productivity regress during the period under study due to technological regress. The results indicate that the domestic banks have exhibited productivity regress due to technological regress, while the foreign banks have exhibited productivity progress attributed to technological progress. Credit risk and diversification have negative impacts on Thailand banks’ total factor productivity. On the other hand, the better capitalized and profitable Thailand banks tend to be relatively more productive. During the period under study, business cycle display mixed impacts. The empirical findings seem to suggest that the different structures of bank ownership have no significant impact on bank productivity.